2003
DOI: 10.1261/rna.2175703
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and structural requirements for optimal guide RNA-directed insertional editing within Leishmania tarentolae

Abstract: The coding sequence of several mitochondrial mRNAs of the trypanosomatid family of protozoa is created by the guide RNA-directed insertion and deletion of uridylates (Us). Selection-amplification was used to explore the sequence and structure of the guide RNA and mRNA required for efficient insertional editing within a mitochondrial extract prepared from Leishmania tarentolae. This study identifies several novel features of the editing reaction in addition to several that are consistent with the previous mutag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Several in vitro studies have shown that when transacting gRNAs are presented in cis they faithfully direct the addition or deletion of uridines at specific sites within the mRNA (Kapushoc and Simpson 1999;Cruz-Reyes et al 2001). Additionally, the 5Ј UTR of some pre-edited mRNAs are known to enhance the activity of nonspecific uridine addition and deletion in adjacent sequences within the mRNA (Connell et al 1997;Pai et al 2003). While highlighting the ability of editing events to be influenced by cis regions, these studies have not directly addressed the ability of a 3Ј UTR to function as a cis-acting guide.…”
Section: Utr Of Coii Functions As a Cis-guiding Elementmentioning
confidence: 99%
“…Several in vitro studies have shown that when transacting gRNAs are presented in cis they faithfully direct the addition or deletion of uridines at specific sites within the mRNA (Kapushoc and Simpson 1999;Cruz-Reyes et al 2001). Additionally, the 5Ј UTR of some pre-edited mRNAs are known to enhance the activity of nonspecific uridine addition and deletion in adjacent sequences within the mRNA (Connell et al 1997;Pai et al 2003). While highlighting the ability of editing events to be influenced by cis regions, these studies have not directly addressed the ability of a 3Ј UTR to function as a cis-acting guide.…”
Section: Utr Of Coii Functions As a Cis-guiding Elementmentioning
confidence: 99%
“…The 39 end of the RNA substrate had been blocked prior to the assay through ligation to the 59 end by treatment with RNA ligase. This circular substrate RNA ensured that the higher-mobility product did not result from the addition of U's to the 39 end by a terminal uridyyl transferase (TUTase) activity that is present within the editing extract (Brown et al 1999;Pai et al 2003).…”
Section: The In Vitro Selectionmentioning
confidence: 99%
“…This is not an intrinsic deficiency of the editing extract as other RNAs are accurately edited by the same in vitro reaction . Rather, it is most likely a reflection of the sequence that was selected upstream of the editing site, which was previously shown to significantly influence editing fidelity (Igo et al 2002;Pai et al 2003). There was not an explicit requirement during the selection to have completely accurate editing provided that any U insertions still triggered a conformational change that activated streptavidin binding.…”
Section: The In Vitro Selectionmentioning
confidence: 99%
See 2 more Smart Citations